PRODUCTION AND CHARACTERIZATION OF MONOCLONAL-ANTIBODY THAT SIMULTANEOUSLY RECOGNIZES METHAMPHETAMINE AND ITS MAJOR METABOLITE - NAM, KS; KIM, JW; CHOI, MJ; HAN, MY; CHOE, IS; CHUNG, TW (PHARMACEUTICAL SOC JAPAN, 1993)
A series of monoclonal antibodies (mAbs) that react with methamphetamine-bovine serum albumin (MA-BSA) were established by intrasplenic immunization method. Among established 36 clones, two typical mAbs, designated NK-1 and NK-2, were described. The inhibition assay of enzyme-linked immunosorbent assay (ELISA) analysis using methamphetamine analogs indicated that NK-1 showed considerable reactivity not only MA-BSA but also methamphetamine and its major metabolite, para-hydroxymethamphetamine (p-hydroxymethamphetamine). The cross-reactivity between NK-1 and the methamphetamine analogs with modified alkyl side chain, indicates that methyl groups of R5 and R7 in the methamphetamine molecules are important for the maximum affinity. The length of alkyl side chain on methamphetamine significantly affected the binding affinity of NK-1. The results may suggest that NK-1 will recognize not only methamphetamine but also the bridge part of the methamphetamine that binds the methamphetamine molecules to a carrier protein.